HARI BUDAYA KABUPATEN KUTAI KARTANEGARA - Awang Muhammad Rifani; Toni Nurhadi Kumayza (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2014)
From the point of history, culture and Kutai already recognizable from the first century BC, as the kingdom and the first country in the Nusantara that Martadipura kingdom. Kutai departing from the history can be called as the base of the civilization of the Nusantara. Long historical journey for the district of Kutai has certain cultural potential that you want to dig back, Momentum history and culture that have occurred in the past need to be a day of reflection in the culture that has benefits for current and future generai to preserve and develop cultural arts.The purpose of this study to determine the exact moment of historic events in the past to be able to serve as an acceptable cultural Today the entire society. Besides, this study intends to reinvent themselves kutai people not to be swayed by the influence of foreign cultures are not necessarily compatible with the spirit and virtue of his own cultureThe results showed besides the anniversary events Tenggarong 28 september, the coronation of the Sultan of Kutai Ing Martadipura to XX on 22 september 2001, and the displacement system of governance of swaprja to kutai district on January 21, 1960, there are at least three events which draw in april used as an alternative to the determination of the culture as follows:Tradition is a big agenda society that pelas years, eating new rice, rice bekepor that occurred during the harvest (april) organized as a sense of an act of gratitude.Marriage Dewa Agung Aji Batara Sakti with Coral Princess Melenu that occurred in April about 1300 BCkutai War, the war between the empire kutai with England, Belgium, and the Netherlands. Heroic war which describes the attitude of rejection towards oppression, colonialism and arbitrariness occurred on 12 April Keywords: Culture Day, Kutai